Penentuan Kecukupan Panas serta Evaluasi Sensori Produk Opor Ayam Steril PT XYZ - Tjahja Muhandri; Putri Aslamiah Zahra; Dian Herawati; Harum Fadhilatunnur (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2024)
Chicken opor, a seasoned dish made with chicken, spices, and coconut milk, has the potential to be developed into a practical and shelf-stable food product using proper preservation technology. Besides utilizing retort pouch packaging, a key factor in processing sterile chicken opor is ensuring an effective sterilization process. This study aimed to evaluate the thermal adequacy of the sterilization process for chicken opor produced by PT XYZ and to assess consumer acceptance of its sensory attributes. The product was packaged in 300 g retort pouches, with 44 units filling the sterilization basket. Heat distribution was tested using 30 temperature sensors, and heat penetration was assessed with 15 sensors placed at various locations in a 50 L pressure cooker. Sensory evaluation was conducted with 75 panelists using a hedonic rating scale. The results showed that heat distribution within the pressure cooker was uniform. The thermal adequacy, necessary to meet the commercial sterility standard, was achieved with a 70 minutes sterilization process after reaching the maximum temperature of 110 °C, yielding a minimum F0 value of 4.8 minutes. The hedonic rating test indicated moderate to high acceptance of PT XYZ's sterilized chicken opor among the panelists.